2022
DOI: 10.1002/nop2.1263
|View full text |Cite
|
Sign up to set email alerts
|

Delirium in elderly postoperative patients: A prospective cohort study

Abstract: Aim To describe the incidence, time in days and risk factors for postoperative delirium in elderly patients. Design Prospective cohort study. Methods Patients over 65 years were daily screened with the 4A's Test and the Delirium Observation Screening Scale for postoperative delirium. A psychiatrist assessed according to the DSM‐V. We performed descriptive and logistic regression analyses. Results From 202 patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 63 publications
0
0
1
Order By: Relevance
“…When compared with younger patients, elderly patients had more complications, primarily due to increased cardiac disease, pulmonary disease, and delirium (Elfrink et al, 2021;Nozawa et al, 2015;Okinaga et al, 2018;Zhou et al, 2006). Some studies have found that increasing age is associated with postoperative delirium (Ishihara et al, 2021;Muzzana et al, 2022). In this study, there was no significant difference in postoperative complications between patients aged ≥85 yr and those aged 70-79 or 80-84 yr. Fortunately, no patients aged ≥90 yr were found to have cardiac or pulmonary complications.…”
Section: Discussioncontrasting
confidence: 47%
“…When compared with younger patients, elderly patients had more complications, primarily due to increased cardiac disease, pulmonary disease, and delirium (Elfrink et al, 2021;Nozawa et al, 2015;Okinaga et al, 2018;Zhou et al, 2006). Some studies have found that increasing age is associated with postoperative delirium (Ishihara et al, 2021;Muzzana et al, 2022). In this study, there was no significant difference in postoperative complications between patients aged ≥85 yr and those aged 70-79 or 80-84 yr. Fortunately, no patients aged ≥90 yr were found to have cardiac or pulmonary complications.…”
Section: Discussioncontrasting
confidence: 47%
“…A prospective cohort study [81] Delirium and long-term psychopathology following surgery in older adults [82] CAM-ICU DSM-V ICD- Postoperative delirium is an independent factor influencing the length of stay of elderly patients in th intensive care unit and in hospital [83] A processed electroencephalogram-based brain anesthetic resistance index is associated with postoperative delirium in older adults: a dual center study [84] Independent external validation of a preoperative prediction model for delirium after cardiac surgery: a prospective observational cohort study [85] Lower preoperative verbal memory performance is associated with delirium after coronary artery bypass graft surgery: a prospective cohort study [86] Effect of regional vs. general anesthesia on incidence of postoperative delirium in older patients undergoing hip fracture surgery [ Lower preoperative serum uric acid level may be a risk factor for postoperative delirium in older patients undergoing hip fracture surgery: a matched retrospective case-control study [90] Risk factors and effect of postoperative delirium on adverse surgical outcomes in older adults after elective abdominal cancer surgery in Taiwan [91] High ASA physical status and low serum uric acid to creatinine ratio are independent risk factors for postoperative delirium among older adults undergoing urinary calculi surgery [92] W wybranej do analizy literaturze najliczniejszą grupę badaną tworzyło 10 755 (36,6%) chorych po operacjach kardiochirurgicznych, a odsetek występowania majaczenia pooperacyjnego dotyczył 2043 chorych. Pozostałe prace dotyczyły odpowiednio 7812 (26,6%) chorych po operacjach ortopedycznych, 5227 (18%) chorych po operacjach brzusznych, 689 (2,3%) chorych po operacjach torakochirurgicznych, 484 (1,6%) chorych po operacjach naczyniowych, 2678 (9,1%) chorych po operacjach neurochirurgicznych, 1714 (5,8%) chorych po operacjach urologicznych.…”
Section: Tytułmentioning
confidence: 99%